Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
You’re supposed to graph the function. So basically you’ll want to make it so that y=, and then the rest of your formula.
So in this case y=3x+9
So in this case y=3x+9
[tex] - 9x + 3y - 27 = 0 \\ a = - 9 \\ b = 3 \\ c = 0 \\ {b}^{2} - 4ac = 9 - 4( - 9)( - 27) = 0 \\ x = \frac{ - b}{2a} = \frac{ - 3}{ - 18} = \frac{1}{6} \\ x = \frac{1}{6} \\ y = ( - 9 \times \frac{1}{6} ) + 3y = 27 \\ \frac{ - 3}{2} + 3y = 27 \\ 3y = 27 + \frac{3}{2 } \\ 3y = \frac{57}{2} \\ y = \frac{57}{6} = \frac{19}{2} \\ [/tex]
i hope it helps u.....
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.